Determinants of spatial market efficiency of grain markets in Russia - Miranda Svanidze; Linde Götz (Food Policy, 2019)
Results of an unobserved effects model on the determinants of inter- and intraregional grain market integration in Russia in comparison to the USA highlights the differences of the mechanisms underlying market integration in each market. Physical trade flows are exclusively dominant in Russia; in contrast, in the United States, additional information flows induced by commodity futures markets play a great role. Policies which improve grain market efficiency in Russia should not only foster investments in transportation and trade infrastructure, but also the development of market information services and commodity futures markets.
Keywords: 330; wheat markets; regional integration; unobserved effects model; Russia; The USA